Pengaruh Gaya Kepemimpinan, Pengembangan Kewirausahaan dan Good Corporate Governance (GCG) terhadap Kinerja Koperasi di Kabupaten Simalungun - Pulungan, Abraham Ismail; Lubis, Zulkarnain; Sibuea, Muhammad Buhari (JURNAL AGRICA, 2024)
Good and professional cooperative management is based on the abilities of each member of the cooperative as well as policies made in meetings and ongoing supervision. The background of this research was conducted to determine the influence of leadership style, entrepreneurial development and good corporate governance on cooperative performance. The method used in this research is a descriptive quantitative research method. The population of this research is KUD cooperatives registered with the Simalungun Regency Cooperative Service, totaling 54 KUDs. The sample used in this research was all cooperatives in Simalungun Regency, totaling 54 people. The sampling method used is total sampling, namely using the entire population as a sample. Data were analyzed using simple regression and multiple regression. The results of this research show that leadership style is in the good category with a percentage of 100%, then entrepreneurship development is in the good category with a percentage of 12%, then good corporate governance is in the good category with a percentage of 19% and cooperative performance is in the quite good category. with a percentage of 53%. The results of the multiple regression test that has been carried out show that there is no positive and significant influence between leadership style, entrepreneurial development and good corporate governance on the performance of cooperatives in Simalungun Regency.